Multicultural Counseling to develop Intercultural Relations - Muslima; Elviana; Maulidia Harza; Emawati; Hamdi Yusliani (JKA, 2024)
Cultural diversity in modern society is growing, characterized by increased interaction between individuals and groups with different backgrounds. It can pose a challenge in communicating and developing harmonious relationships. Multicultural counselling offers an approach that can help develop understanding and skills in cross-cultural interaction. This article examines the concept of multicultural counselling and its mechanisms in facilitating the development of intercultural relationships. Through a review of the literature, it was found that multicultural counseling focuses on the recognition and appreciation of cultural differences, as well as developing the cultural competence of counsellors to provide services that are responsive to the needs of clients with diverse backgrounds. It can help clients understand and appreciate differences, enhance empathy, and develop cross-cultural communication skills.